2020
DOI: 10.20944/preprints202011.0437.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modulation of ATP8B1 Gene expression in Colorectal Cancer Cells Suggest its Role as a Tumor Suppressor

Abstract: Sporadic colorectal cancer (CRC) develops through distinct molecular events. Loss of 18q chromosome is a conspicuous event in the progression of adenoma to carcinoma. There is limited information regarding the molecular effectors of this event. Earlier, we had reported ATP8B1 as a novel gene associated with CRC. ATP8B1 belongs to the family of P-type ATPases (P4 ATPase) that primarily function to facilitate the translocation of phospholipids. In this study, we attempt to implicate ATP8B1 gene located on chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…ATP81 is an oncogene on chromosome 18q that has been found to be associated with a broad range of liver diseases, including cholestasis, progressive familial intrahepatic cholestasis, and benign recurrent intrahepatic cholestasis. In a recent study, Saleh Althenayyan et al found that downregulation of ATP8B1 was associated with the poor prognosis of colorectal cancer, and the upregulated expression of this gene in colorectal cancer cells inhibited their growth and increased the rate of cell apoptosis [43], while the underlying regulatory mechanism was not further explained. Zhang et al demonstrated that ATP8B1 knockdown rstly induced mitochondrial dysfunction, and then, promoted production of reactive oxygen species (ROS) in squamous cell carcinoma of the lung [44].…”
Section: Discussionmentioning
confidence: 99%
“…ATP81 is an oncogene on chromosome 18q that has been found to be associated with a broad range of liver diseases, including cholestasis, progressive familial intrahepatic cholestasis, and benign recurrent intrahepatic cholestasis. In a recent study, Saleh Althenayyan et al found that downregulation of ATP8B1 was associated with the poor prognosis of colorectal cancer, and the upregulated expression of this gene in colorectal cancer cells inhibited their growth and increased the rate of cell apoptosis [43], while the underlying regulatory mechanism was not further explained. Zhang et al demonstrated that ATP8B1 knockdown rstly induced mitochondrial dysfunction, and then, promoted production of reactive oxygen species (ROS) in squamous cell carcinoma of the lung [44].…”
Section: Discussionmentioning
confidence: 99%